2017
DOI: 10.1007/s00426-017-0883-5
|View full text |Cite
|
Sign up to set email alerts
|

Action–effects enhance explicit sequential learning

Abstract: Different studies have shown that action-effect associations seem to enhance implicit learning of motor sequences. In a recent study (Haider et al., Conscious Cognit 26:145-161, 2014), we found indications that action-effect learning might play a special role in acquiring explicit knowledge within an implicit learning situation. The current study aims at directly manipulating the action-effect contingencies in a Serial Reaction Time Task and examining its impact on explicit sequence knowledge. For this purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Thus, there might be a difference in explicit sequence knowledge between groups. The evidence for the relevance of action effects for explicit knowledge of the motor sequence has been shown in several studies (Esser & Haider, 2018;Lustig & Haider, 2019;Tubau, Hommel, & López-Moliner, 2007). Tubau et al (2007) found that response-contingent tone effects facilitate phonetic coding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, there might be a difference in explicit sequence knowledge between groups. The evidence for the relevance of action effects for explicit knowledge of the motor sequence has been shown in several studies (Esser & Haider, 2018;Lustig & Haider, 2019;Tubau, Hommel, & López-Moliner, 2007). Tubau et al (2007) found that response-contingent tone effects facilitate phonetic coding.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this study was the first to investigate the role of action effects on motor sequence performance from multiple sensory modalities perspective. This is an important area, because actions in daily life normally lead to multisensory action effects, including proprioception, vision, and audition, which leads to an activation of a broad network of different modalities (Esser & Haider, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of implicit-learning research, action effects have been shown to enhance implicit sequence learning when participants' own motor responses result in predictable action effects (e.g., Haider et al, 2014). Recent work has suggested that action effects may also be particularly important for transferring learning from implicit into explicit awareness (Esser & Haider, 2017a, 2017b. These findings demonstrate that action-effect associations likely play a central role in establishing the contextual knowledge needed for making action predictions.…”
Section: The Role Of Effects In Continuous Action Sequencesmentioning
confidence: 94%
“…In the former case, it is argued that knowledge can only become explicit when other cognitive systems come into play. Recent findings have shown that sequence learning also results in explicit knowledge depending on the Btask set^-that is, the relation between the stimulus characteristics and the required response of the learner (Esser & Haider, 2017a, 2017b.…”
Section: Relations Between Predictive Gaze Action Performance and Vmentioning
confidence: 99%
“… 10 ]. In addition, multimodal contingent consequences of any responses during learning enhance acquisition of explicit knowledge about a stimulus sequence [ 11 13 ]. Haider and coworkers interpreted this enhancement by way of the ideomotor principle of action control as well as an increased sense of agency, which might trigger a causal inference process [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%